2019
DOI: 10.1101/593582
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Is there more room to improve? The lifespan trajectory of procedural learning and its relationship to the between- and within-group differences in average response times

Abstract: Characterizing the developmental trajectories of cognitive functions such as learning, memory and decision making across the lifespan faces fundamental challenges. Cognitive functions typically encompass several processes that can be differentially affected by age.Methodological issues also arise when comparisons are made across age groups that differ in basic performance measures, such as in average response times (RTs). Here we focus on procedural learning -a fundamental cognitive function that underlies the… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

4
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 60 publications
0
18
1
Order By: Relevance
“…Using hypnosis, Nemeth, Janacsek, Polner, et al (2013) experimentally reduced frontal-lobe connectivity, reducing competition from the attention-based frontal lobe processes, and found increased statistical learning performance compared to an alert, awake state. Additionally, several developmental studies have found that children perform better than adults on statistical learning tasks (Janacsek et al, 2012;Juhasz et al, 2019;Zwart, Vissers, Kessels, & Maes, 2019). Supporting the competition model, the degree of learning drops with the onset of adolescence, coinciding with the maturation of the frontal lobe.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Using hypnosis, Nemeth, Janacsek, Polner, et al (2013) experimentally reduced frontal-lobe connectivity, reducing competition from the attention-based frontal lobe processes, and found increased statistical learning performance compared to an alert, awake state. Additionally, several developmental studies have found that children perform better than adults on statistical learning tasks (Janacsek et al, 2012;Juhasz et al, 2019;Zwart, Vissers, Kessels, & Maes, 2019). Supporting the competition model, the degree of learning drops with the onset of adolescence, coinciding with the maturation of the frontal lobe.…”
Section: Discussionmentioning
confidence: 72%
“…We chose a widely used task for measuring probabilistic statistical learning, namely the alternating serial reaction time task (ASRT, Figure 1A), which has been used in experimental psychology studies (J. H. Howard & Howard, 1997;D. V. Howard et al, 2004;Nemeth et al, 2010;Song, Howard, & Howard, 2007), developmental studies (Janacsek et al, 2012;Juhasz, Nemeth, & Janacsek, 2019;Nemeth, Janacsek, & Fiser, 2013), as well as neuroimaging studies (Bennett et al, 2011;Stillman et al, 2013). The ASRT task is a four-choice reaction time task in which predetermined stimuli alternate with random ones creating a probabilistic structure with more frequent versus less frequent stimulus triplets.…”
Section: Introductionmentioning
confidence: 99%
“…The dissection of the perceptuo-motor adaptation and the statistical aspect of the learning process was also supported by the fact that after the normalization of the baseline RTs, the lack of differences in statistical learning between the single-and the dual-task group remained. As the development of general skill and statistical learning might follow different trajectories (Juhasz, Nemeth, & Janacsek, 2019), this result is crucial for stating that the sequence knowledge is the same between groups. Previous inconsistencies in the literature might also originate from differences in the proportion of general skill-and statistical learning-related factors of the used task.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of research has shown that children (under the age of ~12-13 years) outperform adolescents and adults on learning/memory tasks that require the extraction of predictable patterns from the stimulus stream, which is an important aspect of procedural memory and skill learning (Janacsek et al, 2012;Juhasz, Nemeth, & Janacsek, 2019;Nemeth, Janacsek, & Fiser, 2013;Thompson-Schill, Ramscar, & Chrysikou, 2009). It has been proposed that this behavioral pattern can be explained by a relatively greater reliance on one neural 6 circuitry involved in learning compared to the other due to their different pace of maturation.…”
Section: Competitive Neurocognitive Functions In Typical and Atypicalmentioning
confidence: 99%